CZEGO PRAGNĄ PRZYSZLI FILOLODZY... WYNIKI BADANIA PILOTAŻOWEGO NA TEMAT ŚWIADOMOŚCI WYBORU I OCZEKIWAŃ STUDENTÓW FILOLOGII - Smuk, Maciej (Neofilolog, 2020)
The main of this article is to present the results of a pilot study carried out among 476 students of selected foreign languages at Warsaw University. The research covered the following issues: (1) students’ interest in various courses included in philology studies (literature, linguistics, foreign language didactics, etc.); (2) the dominant motivation for undertaking philological studies and (3) students’ initial career plans. The research is diagnostic and descriptive and it will be continued at over a dozen Polish universities. The main goal of this project is to build a social representation of foreign language studies in Poland today. The Polish Association of Modern Languages (PTN) is a patron of the study.